Stirring up experience through movement in game play: Effects on engagement and social behaviour - Lindley, Siân; Couteur, James Le; Bianchi-Berthouze, Nadia (Proceedings of the 2008 SIGCHI conference on Human Factors in computing systems, 2008)
The recent development of controllers designed around natural body movements has altered the nature of gaming and contributed towards it being marketed as a more social activity. The study reported here compares the use of Donkey Konga bongos with a standard controller to examine how affording motion through an input device affects social interaction. Levels of engagement with the game were also measured to explore whether increases in social behaviour in the ‘real world’ would result in reduced involvement with the ‘game world’. Social interaction was significantly higher when the bongos were used, but this did not detract from engagement. Instead, engagement was also found to increase when body movement was afforded.